Application of a compost with addition of silicon in rose cultivation (Rosa x hybrida) - Mejía-Carranza, Jaime; Cruz-Chávez, David; Alvarado- Hernández, Rafael; Ramírez-Gerardo, Marithza Guadalupe (Ecosistemas y Recursos Agropecuarios, 2022)
Excessive use of agrochemicals to nourish and control pests in rose crops (Rosa x hybrida) entails environmental and economic costs, so alternatives are sought to reduce their use. The objective of this research was to obtain a compost made with vegetables that provide silicon and to evaluate its effect in four productive cycles of rose cv Freedom®, on the incidence of the two-spotted spider mite (Tetranychus urticae), soil properties and flower quality. The experimental design was complete randomized blocks with three repetitions, the treatments were, control without application (T0), compost (T1) and commercial products, Nubiotek Si® (T2) and Silex® + Silifertidol® (T3). The characteristics of the compost were 35% humidity, 24% organic matter and 4.2 dS m−1 of electric conductivity, values within the Mexican regulations, its application significantly improved (P < 0.05) the amount of organic matter, microbial activity in the soil, as well as a longer averagenumber of stems with the presence of mites, however, there was no improvement in the quality of the crop and in the average number of T. urticae. It is concluded that the availability of silicon was limited and therefore, it was not enough to exert a significant effect on the variables evaluated in the cultivation cycles.
Keywords: organic fertilizer, microbial activity, organic matter, quality flower, cv Freedom®